Component fatty acids from green mango fruit surface stimulate oviposition of the mango pulp weevil, Sternochetus frigidus (Fabr.) - De Jesus, L. R. A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
Component fatty acids that influence oviposition of the mango pulp weevil [Sternochetus frigidus (Fabr.)] in bioassays were identified from the hexane extract of 70-d-old green Mangifera indica 'Carabao' fruit peel by gas chromatography-mass spectrometry. Two fractions were found to stimulate oviposition. The fatty acids found common to both active Fractions 5 and 6 were 12:0, 14:0,12-methyl-, 15:0,14-methyl-, 17:0,16-methyl-, 18:1(8) and 18:2 (9,12). The fatty acid 18:3(9,12,15) was found only in Fraction 6. Both fractions had a wide range of activity, 0.01 to 0.05 mango fruit equivalents, resulting in 5.4 eggs laid per female average in a 24-h bioassay, twice the number of eggs laid in the control.